Personality and Headaches: Findings From Six Prospective Studies. Issue 2 (February 2021) - Stephan, Yannick; Sutin, Angelina R.; Luchetti, Martina; Canada, Brice; Terracciano, Antonio
ABSTRACT: Objective: The present study examined the association between personality traits and concurrent and incident headaches. Methods: Participants ( n = 34, 989), aged 16 to 107 years were from the Midlife in the United States study, the Midlife in Japan study, the Health and Retirement Study, the Wisconsin Longitudinal Study Graduate and Siblings samples, and the Longitudinal Internet Studies for the Social Sciences. Demographic factors, personality traits, and headaches were assessed at baseline. Headaches were assessed again 4 to almost 20 years later. Results: Across the samples, higher neuroticism was related to a higher likelihood of concurrent (combined odd ratio = 1.41, 95% confidence interval [CI] = 1.28–1.55, p < .001) and incident (combined odd ratio = 1.28, 95% CI = 1.12–1.46, p < .001) headaches, whereas higher extraversion was associated with a lower likelihood of concurrent (combined odd ratio = 0.87, 95% CI = 0.84–0.89, p < .001) and incident (combined odd ratio = 0.90, 95% CI = 0.85–0.96, p = .001) headaches. Higher conscientiousness (combined odd ratio = 0.90, 95% CI = 0.86–0.94, p < .001) and openness (combined odd ratio = 0.95, 95% CI = 0.90–0.99, p = .025) were associated with a lower probability of reporting concurrent headaches. Agreeableness was unrelated to headaches. Sex was not a consistent moderator. Conclusions: The present study provides robust evidence that neuroticism and introversion are risk factors for headaches in concurrent and prospective analyses across multiple cohorts. Abstract : Supplemental digital content is available in the text.